Format al-Burhan Dalam Tradisi Pengajian Mantik: Tumpuan Khusus Terhadap Teks Kitab al-Mustasfa Min ‘Ilm al-Usul, Karangan al-Imam al-Ghazzali - Hamat, Mohd Fauzi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
This article will analyse the significance of al-Ghazzali's discussion on the various forms of demonstrative (al-burhan) in the light of Islamic tradition. Some selected texts from his book, al-Mustasfa min 'Ilm al-Usul discussing that topic will be translated and discussed academically.